Examining the policies of paroling authorities in the United States to support evidence-based practices - Harbinson, Erin (European journal of probation, 2020)
While much research in community corrections examines ways in which direct supervision can reduce recidivism, less is known about the role of paroling authorities in using or supporting evidence-based practices. This study presents a selection of results from a survey of paroling authorities across the United States conducted in 2015. We analyze and discuss survey results on the following three topics: (1) What is the structure and power/authority of the paroling authorities? (2) What are the appointments and requirements of paroling authorities? and (3) What evidence-based practices are paroling authorities utilizing? These results demonstrate the state of evidence-based practices in parole decision-making and illustrate ways in which paroling authorities can implement policies and practices that promote sustainability of evidence-based practices in community supervision. The findings indicate that many paroling authorities have adopted policies supportive of evidence-based practices; however, there are some areas in which parole can create continuity and promote better application of them.